Empress Dowager Cixi's Imperial Pedagogy: The School for Female Nobles and New Visions of Authority in Early Twentieth Century China. - Barish, Daniel (NAN NU -- Men, Women & Gender in Early & Imperial China, 2018)
After the 1861 coup that brought her to power, Empress Dowager Cixi mobilized a variety of traditions of imperial education to cultivate the persona of a classical ruler and cement her place at the center of Qing governance. At the turn of the twentieth century, however, her enemies launched a propaganda campaign that portrayed Cixi not as a legitimate ruler but as the enemy of progress. In response, Cixi herself began a project to refashion the Qing throne, placing new institutions of imperial education for women at the center of efforts to reestablish her domestic authority and reclaim the Qing's international standing. After reviewing Cixi's strategies of legitimation from 1861 to 1898, this paper focuses on the Empress's twentieth-century attempt to construct an educational apparatus to invent and train a group of female nobles who were intended to play a leading role in reforms around the country. In advocating for the role of these women and institutions, Cixi placed herself and a cosmopolitan cohort of women at the center of plans for China's future. This future was predicated on a refashioned Qing imperial ideology that grounded the legitimacy of the state in part in its participation in global norms and practices of governance. Although the future Cixi imagined for herself and the Qing never materialized, an examination of the project helps shed new light on the politics and culture of the late Qing and beyond.